DEVELOPING KAMPURUI MOTIFS AS A TOURISM PRODUCT TO IMPROVE CREATIVE INDUSTRY MSMES IN SULAA WEAVING VILLAGE - Yusman Sutoyo; Evi Trisetyasi (Journal of Applied Economics in Developing Countries, 2025)
This research aims to examine the development of Kampurui motifs as tourism products to enhance creative MSMEs in the Sulaa weaving village, addressing the research gap between traditional textile preservation and sustainable tourism development. Employing a qualitative descriptive methodology with 30 purposively selected MSME participants, the study demonstrates that Kampurui from Sulaa possesses distinctive characteristics due to its unique weaving process, confirming its viability as a tourism product development opportunity. The research contributes to existing literature by establishing connections between cultural heritage preservation and sustainable tourism through traditional textiles, identifying three distinct types of Kampurui (padamalala/samasili, bhewe Patawala, and Paporoki) and documenting their historical significance as royal attire within the Buton Sultanate along with their two-stage production process. These findings offer practical implications for both policymakers and MSME practitioners, suggesting that investment in traditional craft development can yield sustainable tourism opportunities while maintaining cultural authenticity, thereby creating market differentiation and supporting economic development strategies that integrate heritage preservation with commercial viability.